2013
DOI: 10.1111/iej.12074
|View full text |Cite
|
Sign up to set email alerts
|

The permanent deformation of the self‐adjusting files when used in canals of extracted teeth

Abstract: Deformation of SAF files occurred mainly as detachment of one of the arches or struts at connection points on the odd side of the file. In no case did its mechanical failure result in metal fragment retention in the root canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When mechanical failure of the SAF occurs, it is most often in the form of tears in the lattice [Figure 2c and d ]. [ 13 14 17 25 ] Such failures might be limited to either: (a) Partial detachment of an arch or strut at one end; or (b) full detachment of an arch. [ 25 ] The present study indicated that, in rare cases, true file separation could occur, with the apical part of the file becoming completely detached and remaining in the canal [Figures 1c and 2b ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When mechanical failure of the SAF occurs, it is most often in the form of tears in the lattice [Figure 2c and d ]. [ 13 14 17 25 ] Such failures might be limited to either: (a) Partial detachment of an arch or strut at one end; or (b) full detachment of an arch. [ 25 ] The present study indicated that, in rare cases, true file separation could occur, with the apical part of the file becoming completely detached and remaining in the canal [Figures 1c and 2b ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of the partial detachment of an arch, the file should simply be discarded. In cases of full detachment of an arch, the detached arch is easily washed out, using either the action of SAF irrigation and movement[ 25 ] or ultrasonic-assisted irrigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Farmakis et al . ). Furthermore, various laboratory studies have reported a positive impact of this file in avoiding debris extrusion compared with hand, rotary and reciprocating files during shaping and cleaning procedures (Kocak et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, throughout the instrumentation process, the complementary neutral pressure irrigation system allows the irrigant solution to escape through the openings in the lattice of the file (Hof et al 2010). SAF instrumentation has been reported to result in fewer microcracks and better shaping and cleaning ability, with fewer mechanical failures (Metzger et al 2010a,b, Oguz et al 2012, Farmakis et al 2013. Furthermore, various laboratory studies have reported a positive impact of this file in avoiding debris extrusion compared with hand, rotary and reciprocating files during shaping and cleaning procedures (Kocak et al 2013, De-Deus et al 2014, Ozsu et al 2014, Pawar et al 2015.…”
Section: Introductionmentioning
confidence: 99%